1985
DOI: 10.1038/ki.1985.198
|View full text |Cite
|
Sign up to set email alerts
|

Bone GLA protein in predialysis chronic renal failure. Effects of 1,25(OH)2D3 administration in a long-term follow-up

Abstract: Serum bone GLA protein (BGP) was measured by radioimmunoassay in 42 patients (age, 47.5 +/- 16.6 years; serum creatinine, 4.32 +/- 1.9 mg/dl) with predialysis chronic renal failure (CRF). Nineteen patients were studied within a short period of time, while 23 were followed with repeated measurements of serum BGP, creatinine, iPTH, and alkaline phosphatase (AP) for a mean period of 17.1 +/- 8.1 months. Eleven of these patients were treated with 1,25(OH)2D3 for a mean of 16.8 +/- 6.4 months. In 23 patients at var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 16 publications
1
21
2
Order By: Relevance
“…Others have found a correlation between serum osteocalcin and serum creatinine in adults with predialysis renal failure or in those undergoing hemodialysis (8,(17)(18)(19). As in our study of children on CAPD, Epstein et al (17) found no correlation between serum osteocalcin and creatinine in adults on CAPD.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Others have found a correlation between serum osteocalcin and serum creatinine in adults with predialysis renal failure or in those undergoing hemodialysis (8,(17)(18)(19). As in our study of children on CAPD, Epstein et al (17) found no correlation between serum osteocalcin and creatinine in adults on CAPD.…”
Section: Discussioncontrasting
confidence: 47%
“…When renal function declines to less than 20 ml/min per 1.73 m2, serum concentrations increase and can be 20-50 times higher than normal. The interpretation of osteocalcin levels in those patients with renal osteodystrophy, therefore, is a product of at least two independent determining factors-decreased renal function and increased bone turnover (16)(17)(18). In the present study, we have measured the clearance of osteocalcin in 16 infants and children on CAPD.…”
Section: Discussionmentioning
confidence: 99%
“…High PTH levels have been associated with increased serum levels of osteocalcin [27]; this is probably due to increased bone remodeling. Previous data by others [13] have shown that long-term administra tion of calcitriol to uremic patients decreases serum osteocalcin levels. This change may be the result of a decrease in PTH levels, in order to separate the direct stimulatory effect of calcitriol on osteocalcin production from an opposite effect mediated through a decrease in PTH levels.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, it has been reported that in uremic patients, calcitriol adminis tration leads to a decrease in serum parathyroid hormone (PTH) [13]. In dialysis patients serum osteocalcin levels are elevated as a result both of a decrease in renal clear ance and an increase in its production due to the high bone turnover [12].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation